Molecular regulations of metabolism during immune response in insects - Dolezal, Tomas; Krejcova, Gabriela; Bajgar, Adam; Nedbalova, Pavla; Strasser, Paul (Insect biochemistry and molecular biology, 2019)
Mounting an immune response is an energy-consuming process. Activating immune functions requires the synthesis of many new molecules and the undertaking of numerous cellular tasks and it must happen rapidly. Therefore, immune cells undergo a metabolic switch, which enables the rapid production of ATP and new biomolecules. Such metabolism is very nutrient-demanding, especially of glucose and glutamine, and thus the immune response is associated with a systemic metabolic switch, redirecting nutrient flow towards immunity and away from storage and consumption by non-immune processes. The immune system during its activation becomes privileged in terms of using organismal resources and the activated immune cells usurp nutrients by producing signals which reduce the metabolism of non-immune tissues. The insect fat body plays a dual role in which it is both a metabolic organ, storing energy and providing energy to the rest of the organism, but also an organ important for humoral immunity. Therefore, the internal switch from anabolism to the production of antimicrobial peptides occurs in the fat body during infection. The mechanisms regulating metabolism during the immune response ensure adequate energy for an effective response (resistance) but they must be properly regulated because energy is not unlimited and the energy needs of the immune system thus interfere with the needs of other physiological traits. If not properly regulated, the immune response may in the end decrease fitness via decreasing disease tolerance.
Keywords: Privileged immunity; Animals; energetický metabolismus; přirozená imunita; Adenosine signaling; Insulin resistance; Warburg effect; zvířata; hmyz; Energy Metabolism; Insecta; Disease tolerance; Immunity, Innate; Immunometabolism